An N‐Heterocyclic Carbene Based Silver Precursor for Plasma‐Enhanced Spatial Atomic Layer Deposition of Silver Thin Films at Atmospheric Pressure. Issue 49 (8th November 2018) - Boysen, Nils; Hasselmann, Tim; Karle, Sarah; Rogalla, Detlef; Theirich, Detlef; Winter, Manuela; Riedl, Thomas; Devi, Anjana
Abstract: A new N‐heterocyclic carbene (NHC)‐based silver amide compound, 1, 3‐di‐ tert ‐butyl‐imidazolin‐2‐ylidene silver(I) 1, 1, 1‐trimethyl‐ N ‐(trimethylsilyl)silanaminide [(NHC)Ag(hmds)] was synthesized and analyzed by single‐crystal X‐ray diffraction, 1 H and 13 C NMR spectroscopy, as well as EI mass spectrometry, and subsequently evaluated for its thermal characteristics. This new halogen‐ and phosphine‐free Ag atomic layer deposition (ALD) precursor was tested successfully for silver thin film growth in atmospheric pressure plasma enhanced spatial (APP‐ALD). High‐purity conductive Ag thin films with a low sheet resistance of 0.9 Ω/sq (resistivity: 10 −5  Ωcm) were deposited at 100 °C and characterized by X‐ray photoelectron spectroscopy, scanning electron microscopy, optical transmittance, and Rutherford back‐scattering techniques. The carbene‐based Ag precursor and the new APP‐ALD process are significant developments in the field of precursor chemistry as well as metal ALD processing. Abstract : Without contamination : A new halogen‐ and phosphine‐free carbene‐based silver precursor was developed and successfully utilized in plasma‐enhanced spatial atomic layer deposition at atmospheric pressure, yielding low‐resistivity silver thin films.